The Materialities of Maya: Making Sense of Object-Orientation. - Alt, Casey (Configurations)
This article discusses the concept of object-orientation. The process of computer graphics modeling is often described as an inherently disembodied activity. Initially viewed as an unconstrained realm for sensory experimentation, Virtual Reality has signified for most critics a superficial doubling of surface reality that privileges visuality in such a way as to more strongly foster an eye-mind link that has little, if anything, to do with the particular materialities of human embodiment. The computer software Maya did not spring fully formed from the head of Silicon Valley. Digital media do not just happen; rather, they are constructed through the complex power negotiations of people and groups, each of whom has specific financial, technical, and social interests in how a particular media technology is manifested, marketed, and modified.